2010
DOI: 10.1021/om100003z
|View full text |Cite
|
Sign up to set email alerts
|

1′,1′′′-Bis(ethynyl)biferrocenyl-Bridged Fe(dppe)Cp* Units: Synthesis, Solid-State Structures, and Electronic Couplings

Abstract: Treatment of 1 0 ,1 000 -bis(ethynyl)biferrocene (1) with 2 equiv of FeCl(η 2 -dppe)(Cp*) (2) in the presence of [H 4 N]PF 6 produced the vinylidene complex [1 0 ,1 000 -((Cp*)(η 2 -dppe)FedCdCH) 2 bfc][PF 6 ] 2 (3) (97%, Cp*=η 5 -C 5 Me 5 ; dppe=1,2-bis(diphenylphosphino)ethane; bfc=1 0 ,1 000 -biferrocenyl, (η 5 -C 5 H 4 ) 2 Fe) 2 ), while neutral tetranuclear 1 0 ,1 000 -((Cp*)(η 2 -dppe)Fe-CtC) 2 bfc (4) was obtained from the reaction of 3 with KO t Bu (68%). The IR, 1 H, 13 C, and 31 P NMR, cyclic voltamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 65 publications
(130 reference statements)
4
52
0
Order By: Relevance
“…Accordingly, the second oxidation wave, which corresponds to the sequential oxidation of the second iron end group, is shifted toward positive potential ( E 0 2 – E 0 1 = 0.12 V). The wave separation corresponding to the iron‐centered events is smaller than that in the bis(iron) 7 ( E 0 2 – E 0 1 = 0.26 V)9 but much larger than that in 8 ( E 0 2 – E 0 1 = 0.00 V) 22. Apparently, the TTF core acts as a better electronic coupler than the bfc unit.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Accordingly, the second oxidation wave, which corresponds to the sequential oxidation of the second iron end group, is shifted toward positive potential ( E 0 2 – E 0 1 = 0.12 V). The wave separation corresponding to the iron‐centered events is smaller than that in the bis(iron) 7 ( E 0 2 – E 0 1 = 0.26 V)9 but much larger than that in 8 ( E 0 2 – E 0 1 = 0.00 V) 22. Apparently, the TTF core acts as a better electronic coupler than the bfc unit.…”
Section: Resultsmentioning
confidence: 86%
“…The incorporation of functional groups into the bridge between the redox centers and control of the molecular topology open routes to functional molecules with oriented electron‐transfer capabilities,14,15 switching abilities,16 multipath connections,12,17 optical activities,18,19 or magnetic properties 5,12,20. Recently, it was shown that the 1′,1″′‐biferrocenyl (bfc) unit in the family of complexes [Cp*(dppe)Fe–C≡C–bfc–C≡C–Fe(dppe)Cp*][PF 6 ] n ( 8 [PF 6 ] n , n = 0–4) acts as a molecular relay and mediates electron transfer between the two ends of the molecule by hopping processes 21,22…”
Section: Introductionmentioning
confidence: 99%
“…For neutral 5 b and 12 , as expected, no absorptions between 800 and 3000 nm were detected, whereas mono‐oxidation of 5 b and 12 ( E ≈500 mV vs. Ag/Ag + ) gave mixed‐valent species [ 5 b ] + and [ 12 ] + and hence a broad absorption within this area (800–3000 nm) was observed. A further increase in the potential resulted in a decrease of this band, which is characteristic for intervalence charge transfer excitations (Figure , Figures SI24 and SI25 in the Supporting Information) . Please note that the low Δ E °′ values ( 5 b : 100 mV, 12 : 80 mV) and therefore the small comproportionation constants ( 5 b : K c =70.0, 12 : K c =29.9) lead, in the best case, to a mixture consisting of an equilibrium of 73 % mixed‐valent monocationic [ 12 ] + as well as 13.5 % neutral 12 and di‐cationic species [ 12 ] 2+ each.…”
Section: Resultsmentioning
confidence: 91%
“…Af urtheri ncrease in the potentialr esulted in ad ecrease of this band, which is characteristic for intervalencec harget ransfer excitations (Figure 9, Figures SI24 and SI25 in the Supporting Information). [85][86][87][88][89] Please note that the low DE8' values (5b:1 00 mV, 12:8 0mV) and therefore the small comproportionation constants( 5b: K c = 70.0, 12: K c = 29.9) lead, in the best case, to am ixture consistingo fa ne quilibrium of 73 %m ixed-valent monocationic [12] + as well as 13.5 %n eutral 12 and di-cationic species [12] 2 + each. As the composition of this equilibrium is not determinable by using an OTTLE cell, the extinctionv alues are associated with considerable uncertainties.…”
Section: Resultsmentioning
confidence: 99%
“…We attribute all redox features to the Fe 2+ /Fe 3+ couples . The first redox event is the Fe 2+ /Fe 3+ of one of the ferrocene centres at a lower potential, followed by the second redox event at a higher potential.…”
Section: Resultsmentioning
confidence: 97%